Hubungan Dukungan Sosial Keluarga Dengan Sikap Ibu Dalam Memberikan ASI Eksklusif Dalam Perspektif Agronursing Di Puskesmas Panti Kabupaten Jember - Susanto, Tantut; Kusumaningtyas, Aprilia; Aini Susumaningrum, Latifa (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Psychosocial condition through improvement of mothers’ self-confidence related to providing of exclusive breastfeeding (EBF). Mothers who living in agricultural areas needs family support to support their attitude toward EBF. The aimed of study was to identify the correlation family social support FSS and the attitude of mother toward EBF (AM-EBF). Cross-sectional study design was used to measure 156 mothers which have children age 0-6 mounth, using stratified random sampling. A self-administered questionnaires were measured sociodemographics of mothers and children. FSS was measured using the the Family social Support while AM-EBF was performed using the Maternal Attitudes Towards Breastfeeding Questionnaire. The data were analyzed by Kruskal Wallis test. The results showed that mothers were perceived FSS and AM-EBF were 89,9% , and 90,4% in attitude family. This study conclude that FSS is related with on mother’s attitude in EBF (p-value=0,000). There were significant relationship between family social support and attitude mother. Therefore, family needs guidance inn supporting exclusive breastfeeding and health care service which can help develop family’s involvement in order to support mother’s EBF.